Magnetic Resonance Methods for Focused Ultrasound-Induced Blood-Brain Barrier Opening - Conti, Allegra; Kamimura, Hermes A. S.; Novell, Anthony; Duggento, Andrea; Toschi, Nicola (Frontiers in Physics, 2020)
Since its discovery in 2001, the interest in the low-intensity focused ultrasound (FUS)-mediated blood-brain barrier (BBB) disruption to deliver genes and drugs to brain tissue has increased steadily. Increasingly sophisticated sonication protocols and dedicated hardware are being developed to efficiently and safely permeabilize the BBB, and novel magnetic resonance (MR)-based technologies have been designed to guide FUS-induced BBB opening protocols. MR imaging (MRI) allows not only to more precisely target brain regions and evaluate the outcome of sonication in terms of enhanced BBB permeability but also to control the effects of ultrasound on brain structure and function. This review summarizes the state of the art in current MRI hardware and methods used in BBB opening protocols both in pre-clinical and clinical settings.